2019
DOI: 10.1002/macp.201800575
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Cx(AB)yCx Triblock Silicone Copolymers Utilizing Moisture Mediated Living‐End Chain Extension

Abstract: The physical and chemical properties of silicone block copolymers depend upon the block size and chemical characteristics. Silicone block copolymer synthetic procedures typically involve chain‐growth polymerization techniques that are difficult to control, require low temperatures, inert atmospheres, etc., and which are subject to polymer chain redistribution; the latter process broadens dispersity and leads to the formation of cyclic monomers that must be removed. Once formed, tuning the size of the individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The direct hydrosilylation of 3 with pendent vinyl silicones led cleanly and efficiently to elastomer 13 ( Figure A); a modest RI of 1.44 was observed. As with other aryloxysilanes we have examined, [ 9,41 ] these elastomers were stable to boiling water for 24 h (Supporting Information). In a simple PR process, the reaction between BINOL and pendent HSi homopolymers, e.g., poly(hydromethylsiloxane), or copolymers with Me 2 SiO units led rapidly to foams with the generated hydrogen acting as the blowing agent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct hydrosilylation of 3 with pendent vinyl silicones led cleanly and efficiently to elastomer 13 ( Figure A); a modest RI of 1.44 was observed. As with other aryloxysilanes we have examined, [ 9,41 ] these elastomers were stable to boiling water for 24 h (Supporting Information). In a simple PR process, the reaction between BINOL and pendent HSi homopolymers, e.g., poly(hydromethylsiloxane), or copolymers with Me 2 SiO units led rapidly to foams with the generated hydrogen acting as the blowing agent.…”
Section: Resultsmentioning
confidence: 99%
“…[ 39 ] However, our experience has shown that aryloxysilanes are very stable to hydrolysis even at 100 °C in boiling water or 130 °C in steam. [ 9,41 ]…”
Section: Introductionmentioning
confidence: 99%
“…32 These hydrolysis/condensation processes have been used to make high molecular weight silicones, including those containing -PhMeSiO-blocks. 32,33 Condensation of a silanol and a hydrosilane using the same catalyst has also been used to make alternating copolymers with silphenylene monomers. 34 Chain extension to give higher molecular weight polymers occurs only if water is allowed to very slowly enter the hydrosilane/B(C 6 F 5 ) 3 system, for example, via influx of atmospheric moisture (over the course of days).…”
Section: Introductionmentioning
confidence: 99%
“… 28–31 An analogous but much slower hydrolysis reaction occurs (where water acts in place of the alkoxysilane) to form a silanol (Figure 2b) that, in the presence of additional hydrosilanes, will further condense to form a siloxane bond (Figure 2c). 32 These hydrolysis/condensation processes have been used to make high molecular weight silicones, including those containing ‐PhMeSiO‐ blocks 32,33 . Condensation of a silanol and a hydrosilane using the same catalyst has also been used to make alternating copolymers with silphenylene monomers 34 .…”
Section: Introductionmentioning
confidence: 99%
“…The standard Piers-Rubinsztajn reaction involves the condensation of a hydrosilane (R 3 SiH) and alkoxysilane (R 3 SiOR) to form a siloxane, with subsequent removal of an alkane, RH (R = alkyl/aryl). Knowledge of this mechanism has allowed for the design of controlled synthetic routes to polysiloxanes using B(C 6 F 5 ) 3 as the catalyst (Chojnowski et al, 2005;Rubinsztajn and Cella, 2005;Cella and Rubinsztajn, 2008;Yi et al, 2018;Schneider et al, 2019). The strong affinity of B(C 6 F 5 ) 3 with H 2 O can lead to the formation of Brønsted acids which seems to not be a problem in terms of siloxane or polymer synthesis (Neumann et al, 2004;Chojnowski et al, 2005;Longuet et al, 2007).…”
Section: Introductionmentioning
confidence: 99%